Arithmetic fuchsian groups and space time block codes - Carvalho, E.D.; Andrade, A.A.; Palazzo Jr, R.; Vieira Filho, J. (Computational & applied mathematics, 2011)
In the context of space time block codes (STBCs) the theory of arithmetic Fuchsian groups is presented. Additionally, in this work we present a new class of STBCs based on arithmetic Fuchsian groups. This new class of codes satisfies the property full-diversity, linear dispersion and full-rate. Mathematical subject classification: 18B35, 94A15, 20H10.